PWE-145 Prognostic factors influencing survival after liver resection for colorectal metastasis. (28th May 2012) - John, S K P; Vallance, A; Rehman, S; Robinson, S; Charnley, R; Jaques, B; Manas, D; White, S
Abstract : Introduction: A variety of factors have been identified in the literature which influence survival following resection of colorectal liver metastases (CRLM). The aim of this study was to identify those factors which influence survival in patients undergoing resection of CRLM in a UK centre. Methods: All patients having liver resection for CRLM during an 11-year period up to 2011 were identified from a prospectively maintained database and relevant clinical data retrieved from case records. Prognostic factors analysed included tumour size (>5 cm or <5 cm), lymph node status of primary tumour, margin positivity R1 (<1 mm) or R0, neo-adjuvant chemotherapy (for liver), tumour differentiation, number of liver metastasis (4 or more), preoperative CEA (>200 or <200) and whether metastases were synchronous (ie, diagnosed <12 months) or metachronous to the primary tumour. Overall survival (OS) was compared with Kaplan–Meier plots, log rank test. Multi-variate analysis was performed using Cox regression model (SPSS V.19). p<0.05 considered significant. Results: 432 patients underwent resection of CRLM during this period (67% male; mean age 64.5 years). The overall 5-year survival in this series was 43%. A pre-op CEA>200 was present in 10% of patients and was associated with a poorer 5-year OS (24% vs 45%; p<0.001). A resection margin <1 mm was present in 16% of patients and this had a negative impact on 5 yr OS (15% vs 47%; p<0.001). Tumour differentiation, number, size, presence of biliary or vascular invasion, relationship to primary disease, nodal status of primary, or the use of neoadjuvant chemotherapy had no impact on OS. Multi-variate analysis identified only the presence of a positive resection margin (OR 1.75; p<0.05) and a pre-op CEA>200 (OR 1.88; p<0.01) as independent predictors of poorer OS. Conclusion: Despite the wide variety of prognostic factors reported in the literature we were only able to identify a pre-op CEA>200 and the presence of tumour within 1 mm of the resection margin as being of value in predicting survival. These variables are likely to identify patients who may benefit from intensive follow-up to enable early adjuvant chemotherapy postoperatively. Competing interests: None declared.